Physical and optical characterization of samarium oxide-doped niobium tellurite glasses [electronic resource] - 238145 Nuraffera Mohd. Nasir (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2007